KORELASI ANTARA KEBIASAAN DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PADA PEMBELAJARAN TEMATIK KELAS IV - Dea Amelia Rizki; Kartono Kartono; Tahmid Sabri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aimed to analyze the correlation between habits and learning motivationwith learning outcomes of IV grade student at SDN 32 Pontianak Tenggara. Theresearch method used was descriptive research with a correlation study form. Thepopulation in this study were students of grade IV SDN SDN 32 Pontianak Tenggara,totaling 28 students. The sample in this study used a total sample of 28 students. Theresult showed that learning habits was 78,03%, learning motivation was 77,82%, andlearning outcomes obtained an average of 74,25. Statistical calculations using theproduct moment correlation formula that learning habits and learning outcomesobtained rcount 0,65, learning motivation and learning outcomes obtained rcount 0,54,habits and learning motivation obtained rcount 0,55. Habits and learning motivationwith learning outcomes used the multiple correlation formula obtained Ryx1x2 0,54with a moderate level relationship. Fcount 5,14 and Ftable α = 5% is 3,38 which meansFcount (5,14) > Ftable (3,38), then Ha is accepted. So, it can be concluded that there isa relationship between habits and learning motivation with learning outcomes inthematic learning of IV SDN SDN 32 Pontianak Tenggara.Keywords: Correlation, Habits, Learning Outcomes, Motivation